Course of neuropsychological impairment during natalizumab‐associated progressive multifocal leukoencephalopathy. (8th December 2020) - Kinner, Markus; Prehn, Christian; Schneider, Ruth; Schroeder, Christoph; Kolb, Eva; Gold, Ralf; Hoepner, Robert; Chan, Andew
Abstract: Background and purpose: Progressive multifocal leukoencephalopathy (PML), an opportunistic infection of the central nervous system from the John Cunningham virus (JCV), is a side effect of natalizumab (NTZ) treatment for relapsing–remitting multiple sclerosis (RRMS), potentially leading to a substantial increase of physical and mental disability. Nevertheless, data of neuropsychological impairment during the NTZ‐PML disease course are missing. Our objective was to evaluate the neuropsychological disease course of NTZ‐PML patients and to compare neuropsychological deficits of NTZ‐PML patients with two different non‐PML multiple sclerosis (MS) cohorts. Methods: Neuropsychological examinations of 28 NTZ‐PML patients performed during different phases of the disease ([i] at PML diagnosis, [ii] during immune reconstitution inflammatory syndrome [IRIS], and [iii] post‐IRIS/PML) were retrospectively analyzed and compared to those of NTZ‐treated RRMS or secondary progressive MS patients with and without immunotherapy. Results: Compared to controls, NTZ‐PML patients performed worse in neuropsychological examinations during all stages of disease, mainly affecting visuospatial ability and working memory. Furthermore, failure to eliminate the JCV from the central nervous system was associated with a progredient decline of cognition, especially working memory. Conclusions: Working memory and visuospatial abilities are the core neuropsychological deficits of NTZ‐PML patients in long‐term follow‐up. Our findings should be implemented in neurorehabilitation strategies. Abstract : Working memory and visuospatial abilities are found to be core neuropsychological deficits in natalizumab‐induced progressive multifocal leukoencephalopathy (PML). This first evaluation of the neuropsychological disease course in comparison to two non‐PML multiple sclerosis cohorts shows these core deficits in a long‐term follow‐up. Patients with failure to eliminate the John Cunningham virus from the central nervous system showed a progredient cognitive decline, especially in working memory.